2020
DOI: 10.1002/lt.25724
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Quality of Life and Decrease in Large‐Volume Paracentesis Requirements With the Automated Low‐Flow Ascites Pump

Abstract: The automated low-flow ascites pump (alfapump) is an implantable device that drains ascites directly into the urinary bladder. We studied its safety (absence of serious complications) and efficacy (decreased large-volume paracentesis [LVP] requirement and improved quality of life [QoL]) in the management of ascites in a cohort of North American patients with cirrhosis and recurrent ascites ineligible for transjugular intrahepatic portosystemic shunt (TIPS). QoL was measured by the Chronic Liver Disease Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 25 publications
1
37
0
2
Order By: Relevance
“…
We read with great interest the multicenter, openlabel study of the automated low-flow ascites pump (alfapump) system in cirrhosis with recurrent ascites (Multicenter, Open-Label Study of the Automated Low-Flow Asciites Pump [Alfapump] System in Cirrhosis [MOSAIC] study) by Wong et al in which they described the safety and efficacy of the alfapump system for control of refractory ascites in a North American cohort. (1) In this study, the alfapump system, which was inserted by an interventional radiologist using a minimally invasive technique, yielded similar technical success as compared with surgical insertion techniques used in previous studies. They demonstrated that the alfapump system was not only effective in reducing the requirement for large-volume paracentesis (LVP) but also led to significant improvement in quality of life (QoL) of patients with refractory ascites.
…”
mentioning
confidence: 62%
“…
We read with great interest the multicenter, openlabel study of the automated low-flow ascites pump (alfapump) system in cirrhosis with recurrent ascites (Multicenter, Open-Label Study of the Automated Low-Flow Asciites Pump [Alfapump] System in Cirrhosis [MOSAIC] study) by Wong et al in which they described the safety and efficacy of the alfapump system for control of refractory ascites in a North American cohort. (1) In this study, the alfapump system, which was inserted by an interventional radiologist using a minimally invasive technique, yielded similar technical success as compared with surgical insertion techniques used in previous studies. They demonstrated that the alfapump system was not only effective in reducing the requirement for large-volume paracentesis (LVP) but also led to significant improvement in quality of life (QoL) of patients with refractory ascites.
…”
mentioning
confidence: 62%
“…Although survival is a strong primary endpoint it should probably not be the primary endpoint of choice in these trials. Interventions for the management of refractory ascites may not increase survival, particularly in patients who are not candidates for liver transplantation, but may improve the control of ascites or HRQOL, [88][89][90] which are clinically meaningful endpoints in this population.…”
Section: Diuretic-responsive Ascitesmentioning
confidence: 99%
“…However long term studies with larger patient populations are ongoing which will further establish main concerns about such a system, especially pump dysfunction (pump failure and bladder and peritoneal catheter related problems), infection, ascitic fluid leakage through wounds, bladder perforation and renal impairment. 68 - 73 …”
Section: Refractory Ascitesmentioning
confidence: 99%
“…However long term studies with larger patient populations are ongoing which will further establish main concerns about such a system, especially pump dysfunction (pump failure and bladder and peritoneal catheter related problems), infection, ascitic fluid leakage through wounds, bladder perforation and renal impairment. [68][69][70][71][72][73] Recommendations: The incidence of SBP in cirrhotic patients in Pakistan averages 27-38 % of all patients admitted to hospitals, as noted in various studies. [74][75][76][77][78] Up to 10% of asymptomatic patients with cirrhosis presenting for routine outpatient checkups have been found to have SBP.…”
Section: Recommendationmentioning
confidence: 99%